Whence Consumer Loyalty? - Oliver, Richard L. (Journal of Marketing, 1999)
Both practitioners and academics understand that consumer loyalty and satisfaction are linked inextricably. They also understand that this relation is asymmetric. Although loyal consumers are most ...